2015
DOI: 10.3174/ajnr.a4537
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative MR Imaging of Spontaneous Transdural Spinal Cord Herniation: Expected Findings and Complications

Abstract: BACKGROUND AND PURPOSE: Spontaneous transdural spinal cord herniation is no longer a rare cause of myelopathy. The high frequency of diagnoses has led to an increase in the number of surgical procedures. The purpose of this study was to describe the spectrum of postoperative MR imaging findings concerning spontaneous transdural spinal cord herniation and to provide a practical imaging approach for differentiating expected changes and complications after an operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…In recent years, several reports have described postoperative ventral CSF collections, [1][2][3]6 indicating that they may be caused by subsequent CSF leakage through the dural defect. The first report of postoperative ventral CSF collection was written by Nakamura et al 6 and described sixteen patients with ISCH treated by enlargement of the dural defect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, several reports have described postoperative ventral CSF collections, [1][2][3]6 indicating that they may be caused by subsequent CSF leakage through the dural defect. The first report of postoperative ventral CSF collection was written by Nakamura et al 6 and described sixteen patients with ISCH treated by enlargement of the dural defect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, few studies have investigated the long-term outcomes and MRI findings of postoperative changes in the spinal cord or surrounding structures. 1 In recent years, several reports have described postoperative ventral cerebrospinal fluid (CSF) collections in patients with ISCH. 1,6,7 However, these collections are asymptomatic in most patients, and whether they are part of the natural history or a complication remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Complications from such procedures may include anterior epidural CSF collection and superficial siderosis. 5 Direct visualization of the DAW remains difficult using conventional imaging techniques. A web was not confidently identified in any of the 14 cases reported by Reardon et al 12 and was identified in only 2 of 7 cases by Hakky et al 8 Improved visualization of these webs may be achieved by the addition of "myelographic" high-resolution T2-weighted MRI sequences 6 such as constructive interference in steady state (CISS) or SPACE, or their equivalents (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SS may be detected in cortical sulci, interhemispheric fissure, or the Sylvian fissure. Possible pathogenetic causes include bleeding from spinal epidural fistulas, arteriovenous malformations, intracranial aneurysms, tumors, and CAA, as mentioned before [1,8,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%